Evaluating effect of a new sterile gauze containing Bentonite and Halloysite minerals on blood coagulation and wound healing in male rats - Mehrosadat Alavi; Farshid Gheisari; Mahdi Haghighatafshar; Mohammad Ali Okhovat; Peyman Rezaei; Alireza Totonchi; Mohammad Atefi (Iranian South Medical Journal, 2014)
Background: In recent years, a wide variety of researches are performed in the field of novel technologies to stop severe bleeding. Finally, an effective combination of a mineral called Zeolite has been introduced. Bentonite and Halloysite ores are very common in Iran. Likewise, coagulation properties of these minerals have been proven in several studies. In this study, the effect of new recombinant gauze, containing Bentonite and Halloysite minerals was studied on blood coagulation and wound healing time in male rats. Materials and methods: In this exprimental study, new sterile gauze was prepared from mixture of Bentonite and Halloysite minerals and Vaseline. Then the effect of gauze was studied on the wound healing process in the Wistar rat. Finally, SPSS software was used for data analysis (T-test and the nonparametric Mann-Whitney). Differences with P <0.05 were considered as significant. Results: In the first phase, the study was carried out on 40 blood samples of mice tails. The coagulation time of 81.31 ± 19.12 sec in control group and 33.2 ± 2.18 sec in study group (Bentonite-Halloysite treated) were reported. In the second phase, the time of complete wound healing was considered. This figure was observed between 9 and 13 days in the control group and 5 to 6 days in study group which is treated with recombinant sterile gauze. Conclusion: According to the results of the present study, topical application of the new sterile gauze, combined with Bentonite and Halloysite minerals decrease clotting and wound healing time significantly